revelation in the Holy Quran And the position of the orientalists of it (Journal of the College of Basic Education, 2022)
God, the Blessed and Exalted, chose man from among all his creatures and made him and his descendants his successors on earth.He endowed him with the highest of the faculties that raised him to the rank of dignity and honor, and singled him out for reason above all his creatures.He entrusted him with carrying the trust, which no one else could, and since human minds are insufficient to comprehend the virtues ofthings and their disadvantages, as they are incapable of achieving their objectives. Unless he resorts to hidden powers that manage the affairs of